Conversion of Anthranilate Synthase into Isochorismate Synthase: Implications for the Evolution of Chorismate‐Utilizing Enzymes. Issue 38 (14th September 2015) - Plach, Maximilian G.; Löffler, Patrick; Merkl, Rainer; Sterner, Reinhard
Abstract Chorismate‐utilizing enzymes play a vital role in the biosynthesis of metabolites in plants as well as free‐living and infectious microorganisms. Among these enzymes are the homologous primary metabolic anthranilate synthase (AS) and secondary metabolic isochorismate synthase (ICS). Both catalyze mechanistically related reactions by using ammonia and water as nucleophiles, respectively. We report that the nucleophile specificity of AS can be extended from ammonia to water by just two amino acid exchanges in a channel leading to the active site. The observed ICS/AS bifunctionality demonstrates that a secondary metabolic enzyme can readily evolve from a primary metabolic enzyme without requiring an initial gene duplication event. In a general sense, these findings add to our understanding how nature has used the structurally predetermined features of enzyme superfamilies to evolve new reactions.